SeDiCreSig Method (See, Discuss, Create, Simulate, Generalize) to Improve Analysis Ability of Elementary School Teacher Students - Ryan Dwi Puspita; Silvya Rabbani (Jurnal Ilmiah Sekolah Dasar, 2023)
The low ability to analyze learning models will be an obstacle for PGSD (Primary School Teacher Education) students in choosing and implementing learning models that match the learning materials and student characteristics. To improve the analytical skills of PGSD students, the SeDiCreSig method was applied. This study aims to analyze the analytical skills of PGSD students regarding innovative learning models in mathematics in elementary schools (SD) using the SeDiCreSig method. The research method used was quasi-experimental with a pretest-posttest control group design. The population in this study are all 5th-semester PGSD students. The sample used in this study was 70 PGSD students divided into two classes taking the Mathematics Internship course. The data collection techniques used in this study were observation, pretest, and posttest. The data were analyzed by the SPSS 23-assisted t-test. The results of this study indicated an increase in the ability of PGSD students to analyze innovative mathematical learning models after learning using the SeDiCreSig method. The use of the SeDiCreSig method makes it easier for lecturers to direct students in practicing analytical skills and implementing innovative learning models, especially in learning mathematics. The success of learning the SeDiCreSig method must be supported by actual activities that students directly carry out.